LGBTQ Role Models and Curricular Controversy in Canada: A Student Symposium - Boulay, Nadine; Yeung, Betty; Leung, Charmaine; Burns, David P. (Paideusis, 2014)
As a subject for philosophizing about education, there are few topics as rich and significant as the role of public schools in fostering respect for sexual and religious diversity. The liberal state, it is said, has a clear mission to teach students to respect the rights of others to lead fundamentally different ways of life, and to provide students with the tools needed to make similarly fundamental choices about their own lives. The liberal state must do this, however, without undue or excessive infringement on the rights of children and parents who believe that some common ways of life are, writ large, morally objectionable. This symposium paper features three arguments, each formulated by a different student in education or a related field. The first argues that LGBTQ role models must be provided in schools (through school resources or in person). The second argues that teachers are being placed in a very difficult position when such provision causes controversy with the surrounding community. The third argues that parents must not be given unchecked power over their children’s exposure to LGBTQ role modeling.